Nilai-nilai olahraga dan dukungan sosial: Sebuah studi korelasi - Shofie Amalia Vega; Amung Ma’mun; Nuryadi Nuryadi; Syarifatunnisa Syarifatunnisa; Anira Anira (Universitas Nusantara PGRI Kediri, 2025)
The correlation between teenagers' sporting ideals and perceived social support from family, friends, and others is examined in this paper. From a stratified random sample, 1,454 teenagers aged 12–18 (50.1% male and 49.9% female) underwent quantitative research using a correlational survey methodology. While the Multidimensional Scale of Perceived Social Support (MSPSS) evaluated degrees of social support, the Youth Sport Values Questionnaire-2 (YSVQ-2) measured sports values. Using Pearson correlation, data were examined. Sports values and social support had a noteworthy but modest positive connection (r = 0.268, p = 0.001). Among the sources of encouragement, the influence of physical education instructors and coaches was more noticeable than that of family or friends. These findings imply that encouraging good youth development depends on using value-based sports education, particularly via organized programs and motivating adult figures. This study adds to the increasing corpus of research on sports pedagogy and emphasizes how social environments shape teenage ideals using sports.